(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This publication, which includes two parts, draws up the list of the genera of the hosts-plants of the Diptera Agromyzidae. After a short introduction and a presentation of the method the authors give, in the first part, a table with the alphabetical list of the genera and species of Agromyzidae whose hosts-plants are known. In addition to the mention, following each species of Agromyzidae, of the botanical genera hosts, the general biogeographic data are specified for each species of these Dipterous. The second part of this publication will include the alphabetical list of the botanical families and hosts-genera and the species of Agromyzidae which are theirs are associated. On the whole 1285 species of Agromyzidae are listed like 146 botanical families and 899 botanical genera.